Synthesis, characterization and in vitro evaluation of manganese ferrite (MnFe2O4) nanoparticles for their biocompatibility with murine breast cancer cells (4T1) - Kanagesan, Samikannu; Ab. Aziz, Sidek; Hashim, Mansor; Ismail, Ismayadi; Subramani, Tamilselvan; Mohammed Alitheen, Noorjahan Banu; Swamy, Mallappa Kumara; Rao, Bandaru Purna Chandra (MDPI, 2016)
Manganese ferrite (MnFe2O4) magnetic nanoparticles were successfully prepared by a sol-gel self-combustion technique using iron nitrate and manganese nitrate, followed by calcination at 150 °C for 24 h. Calcined sample was systematically characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and vibrational sample magnetometry (VSM) in order to identify the crystalline phase, functional group, morphology, particle size, shape and magnetic behavior. It was observed that the resultant spinal ferrites obtained at low temperature exhibit single phase, nanoparticle size and good magnetic behavior. The study results have revealed the existence of a potent dose dependent cytotoxic effect of MnFe2O4 nanoparticles against 4T1 cell lines at varying concentrations with IC50 values of 210, 198 and 171 μg/mL after 24 h, 48 h and 72 h of incubation, respectively. Cells exposed to higher concentrations of nanoparticles showed a progressive increase of apoptotic and necrotic activity. Below 125 μg/mL concentration the nanoparticles were biocompatible with 4T1 cells.